2018
DOI: 10.1080/03601234.2018.1438836
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of antibiotic resistance genes and encoding ribosomal protection proteins gene in livestock waste polluted environment

Abstract: The rapid development and increase of antibiotic resistance are global phenomena resulting from the extensive use of antibiotics in human clinics and animal feeding operations. Antibiotics can promote the occurrence of antibiotic resistance genes (ARGs), which can be transferred horizontally to humans and animals through water and the food chain. In this study, the presence and abundance of ARGs in livestock waste was monitored by quantitative PCR. A diverse set of bacteria and tetracycline resistance genes en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The figure also shows that tetO and tetW were strongly correlated to each other, which could be explained by its high similarity of amino acid sequences between TetO and TetW, which were categorized into the same group based on the amino acid sequence similarity [8]. The results of this study in terms of the frequency of detection of the RPP tet genes showed that tetO and tetQ, were not as prevalent in the agricultural sites evaluated compared to previous agricultural sites evaluated in previous studies [10,13,36]. The widespread detection of tetW in both arable land and livestock farms was in agreement with other studies [11,13,36], while the infrequent detection of tetS in the agricultural areas of study coincided with the results obtained by Wu et al [10].…”
Section: Tetracycline-resistant Genessupporting
confidence: 47%
See 1 more Smart Citation
“…The figure also shows that tetO and tetW were strongly correlated to each other, which could be explained by its high similarity of amino acid sequences between TetO and TetW, which were categorized into the same group based on the amino acid sequence similarity [8]. The results of this study in terms of the frequency of detection of the RPP tet genes showed that tetO and tetQ, were not as prevalent in the agricultural sites evaluated compared to previous agricultural sites evaluated in previous studies [10,13,36]. The widespread detection of tetW in both arable land and livestock farms was in agreement with other studies [11,13,36], while the infrequent detection of tetS in the agricultural areas of study coincided with the results obtained by Wu et al [10].…”
Section: Tetracycline-resistant Genessupporting
confidence: 47%
“…The results of this study in terms of the frequency of detection of the RPP tet genes showed that tetO and tetQ, were not as prevalent in the agricultural sites evaluated compared to previous agricultural sites evaluated in previous studies [10,13,36]. The widespread detection of tetW in both arable land and livestock farms was in agreement with other studies [11,13,36], while the infrequent detection of tetS in the agricultural areas of study coincided with the results obtained by Wu et al [10]. It is important to note that one animal house in Iksan was found to be negative for the presence of any RPP tet genes.…”
Section: Tetracycline-resistant Genesmentioning
confidence: 55%
“…The members of another group of ABC resistance proteins, included in the (putative) drug resistance ATPase families (also called ABC-F proteins), consist of two fused NBDs. Although they were originally reported as putative efflux pumps, possibly interacting with unidentified TMDs, these proteins have since been confirmed to function in ribosomal protection, and their apparent efflux phenotype is likely to be related to displacement of ribosome-targeting antibiotics from the ribosome. …”
Section: The Movement Of Small Molecules Across Bacterial Cell Envelopesmentioning
confidence: 99%
“…143,144 Resistance to an antibiotic develops via several mechanisms including (but not limited to) the activation of antibiotic transporters (efflux pumps), the production of enzymes to inactivate antibiotics, and modification of the target (active) site of the antibiotic. 145 These mechanisms occur via either spontaneous mutations, through the acquisition of antibiotic resistance genes (ARGs) from other bacteria through horizontal gene transfer (HGT), 146 or through infection via bacteriophages. 147 Often the pathogens acquire multi-drug resistance which complicates treatment and leads to poor patient prognosis.…”
Section: Soil Microorganisms and Human Health Current Statusmentioning
confidence: 99%